NIR/PH-responsive erythrocyte membrane-camouflaged metal-organic framework for photothermal therapy of pancreatic cancer. (March 2023) - Wang, Kai-fei; Mu, Yi-ping; Wang, Shu; Song, Yin-xue; Xu, Jing; Li, Xiao-hui; Wang, Rui-tao
Abstract: Pancreatic cancer is the most malignant tumor in the digestive system. Its strong invasiveness and difficulty of surgical removal result in a high mortality rate. We developed an erythrocyte membrane-camouflaged metal-organic framework (ICG@RB-MOF) loaded with indocyanine green (ICG) for photothermal therapy of pancreatic cancer. ICG can be released in acidic tumor environments due to its pH responsiveness. More importantly, integrating erythrocyte membrane surface modification, immune escape, and prolonged blood circulation characteristics significantly improved the tumor-targeting ability of ICG@RB-MOF. The in vitro and in vivo results demonstrated that the prepared ICG@RB-MOF exhibited a significant therapeutic effect on pancreatic cancer. Graphical Abstract: ga1